Structural-Functional Patterns of Lesions of the Main Arteries of the Head in Patients with Headache - Kalashnikov, Valeriy Y.; Stoyanov, Olexander M.; Oprya, Yevgen V.; Melnyk, Yuriy V. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Aim. To study the structural and functional features of the main arteries of the head (MAH) in patients with migraine (M), tension-type headache (TTH), and cervicogenic headache (CH). Materials and Methods. A total of 456 patients (18–44 years old; 203 men, 255 women) with various types of headaches were studied, including M – 124 people, TTH – 186, and CH – 146 people. Using the duplex scanning method, the structure of the MAH, systolic linear blood flow velocity (Vs), and resistance indices (RI) in the common carotid (CCA), external carotid (ECA), internal carotid (ICA), and vertebral arteries (VA) in V2 segments were assessed. Results. Extravasal compression of the vertebral arteries was significantly more prevalent in patients with CH (43.1%) and M (29.0%), while hypoplasia of the vertebral arteries was found equally in these groups. In all types of headaches, a decrease in velocity indicators and an increase in resistance index values in the VA were noted. In patients with migraine with aura (MA), extravasal compression and hypoplasia of the vertebral arteries predominated, and Vs indicators in this group were significantly reduced. Signs of extravasal compression and the associated decrease in VA hemodynamics were observed in all variants of TTH. Furthermore, signs of extravasal compression of the VA were detected in a significant proportion of patients with CH, especially those with cervicocranialgia (CCrA) and Barré-Liéou syndrome (BLS). In BLS, signs of pathological tortuosity and hypoplasia of the VA predominated. Velocity indices in extracranial segments of the VA were reduced in patients with CCrA and BLS, and a significant increase in RI values was also observed in the BLS group (0.87 ± 0.05; CG – 0.65 ± 0.06; p < 0.05). Conclusions. Patients with M were characterized by the presence of extravasal compressions and a decrease in Vs in the VA. Hypoplasia of the VA was more common in the group of patients with MA than in M without aura. Patients with TTH had a tendency towards reduced velocity indices in extracranial segments of the VA. Patients with CH manifested extravasal compression of the vertebral arteries. Tortuosity and hypoplasia of the VA, in combination with an increase in RI indices, were characteristic of patients with BLS